(‒)-Pteroside N and pterosinone, new BACE1 and cholinesterase inhibitors from Pteridium aquilinum. (October 2018) - Choi, Yun-Hyeok; Choi, Chun Whan; Kim, Jin Kyu; Jeong, Wonsik; Park, Gil Hong; Hong, Seong Su
Graphical abstract: Highlights: A new pterosin glycoside and a new seco -illudoid sesquiterpene were isolated from the Pteridium aquilinum . Compounds1 and2 showed inhibitory activity against BACE1 and cholinesterase. Compound2 was a mixed-type inhibitor against human BACE1 binding to active sites of corresponding enzymes. Structure elucidation was based on spectroscopic data (1D, 2D NMR and HRMS). Abstract: Bioassay-guided fractionation of the ethanolic extract from the whole plants of Pteridium aquilinum has resulted in the isolation of a new pterosin glycoside, (‒)-pteroside N (1 ), and a new seco -illudoid sesquiterpene, pterosinone (2 ). Their structures were identified by analysis of the spectroscopic data including extensive 2D NMR. All of the isolates were evaluated for the anti-Alzheimer disease (anti-AD) activity through enzyme inhibition of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and β-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1). (‒)-Pteroside N (1 ) showed moderate BACE1 inhibitory activity (IC50 value: 30.6 μM), but exhibited potent inhibitory activity against AChE and BChE (IC50 values: 4.47 and 7.39 μM, respectively). On the other hand, pterosinone (2 ) showed mild AChE and BChE inhibitory activity (IC50 value: 87.7 and 72.9 μM), but exhibited potent inhibitory activity against BACE1 (IC50 value: 19.4 μM). The results of the present study demonstrate that sesquiterpenoids from P. aquilinum might be beneficial in the treatment of AD.